Papillon Nuclear Data Library – a free and open-source C++/Python library for interacting with ACE files for continuous-energy neutron data - Belanger Hunter (EPJ Nuclear Sciences & Technologies, 2023)
In this paper, a new C++ and Python library, called the Papillon Nuclear Data Library, is presented. This library gives users a simple interface to read and interact with continuous-energy neutron data in the form of ACE files. Using the library, one can easily evaluate or plot cross-sections for different nuclides and reactions, or sample scattering distributions. Currently, all continuous-energy neutron physics is implemented, and the library can read free-gas neutron and thermal scattering law ACE files. The Python interface makes using nuclear data easy and accessible for students, while the C++ interface gives experienced researchers easy access to continuous-energy physics when writing Monte Carlo codes to test new computational methods.